Makna Teologis Frasa Kami Adalah Hamba yang tidak Berguna dalam Injil Lukas 17:7-10 - Frans Aliadi (Sekolah Tinggi Teologi Nusantara, 2024)
The phrase “we are useless servants” often causes confusion: does this suggest that our service has no meaning or value? In this era, where the success of a servant of God is often measured by awards, recognition, or large profits, the concept of a